Anti-influenza virus effects of crude phenylethanoid glycosides isolated from ligustrum purpurascens via inducing endogenous interferon-γ. (17th February 2016) - Hu, Xiao-peng; Shao, Min-ming; Song, Xun; Wu, Xu-li; Qi, Ling; Zheng, Kai; Fan, Long; Liao, Cheng-hui; Li, Chen-yang; He, Jiang; Hu, Ying-jie; Wu, Hai-qiang; et al.
Abstract: Ethnopharmacological relevance: Ligustrum purpurascens Y.C. Yang (Oleaceae) is traditionally recorded as "Ku Ding Cha", a kind of functional tea in southern China for about two thousand years, which has been reported with sore throat alleviating and pathogenic heat expelling effects. However, there are no scientific studies demonstrating its antiviral activity. The aim of the study: This study is aimed at investigating the anti-influenza virus effects of phenylethanoid glycosides isolated from L. purpurascens (LPG) as well as its corresponding mechanisms. Materials and methods: In vitro, hemagglutination assay was employed to detect the influenza virus titer; In vivo, C57BL/6J mice were given oral administration of LPG (100 mg/kg, 300 mg/kg, 900 mg/kg) or ribavirin (100 mg/kg) once daily for 5 successive days. Meanwhile, on the second day, mice were infected intranasally (i.n.) with A/FM/1/47 H1N1 virus. Mice survival rate and other clinical index were monitored for 15 days. Infected mice were sacrificed to measure the lung lesion and stained with hematoxylin–eosin. Flow cytometry analyses spleen lymphocytes and interferon-γ (IFN-γ) level. The IFN-γ knockout mice (IFN-γ −/− mice, C57BL/6J) which had been verified lacking IFN-γ through Western Blot, were applied in the death-protection test to identify the role of IFN-γ played in LPG antiviral effect. Results: In vitro, LPG at 0.5 mg/ml inhibited Influenza A Virus H1N1 type (H1N1) infection of MDCK cells. In vivo, LPG at 300 and 900 mg/kg significantly decreased the mouse lung index ( p <0.05), alleviated influenza-induced lethality and clinical symptoms, and therefore enhanced mouse survival ( p <0.05). More detailed experiments demonstrated that antiviral cytokine IFN-γ was involved in the antiviral effect of LPG. Flow cytometric analysis revealed that LPG (900 mg/kg) significantly induced secretion of IFN-γ by splenic CD4 + and CD8 + cells ( p <0.05). Moreover, LPG (900 mg/kg) protected wild-type C57BL/6J mice from H1N1 injury, whereas LPG-mediated survival protection disappeared in IFN-γ −/− mice. Conclusion: These results suggest that up-regulating endogenous IFN-γ by LPG may represent a novel therapeutic approach for H1N1 infection. Graphical abstract: